Long-term results of total knee arthroplasty in hemophilic arthropathy - Marta Santos Silva; Ricardo Rodrigues-Pinto; Cláudia Rodrigues; Sara Morais; José Costa e Castro (Journal of Orthopaedic Surgery, 2019)
Purpose: Knee arthropathy is a frequent complication affecting hemophilic patients, which can cause severe pain and disability. When conservative measures fail, total knee arthroplasty (TKA) may be performed. Methods: Eighteen TKA were performed in 15 patients with hemophilia during a 24-year period in a Hemophilia Comprehensive Care Center. All patients were evaluated by a multidisciplinary team constituted by a hematologist, an orthopedic surgeon, and a physical medicine and rehabilitation physician. Mean follow-up was 11.3 years. Results: Ten-year survival rate with prosthesis removal as end point was 94.3%. At last, follow-up visual analog pain scale score was 3.2 points, knee osteoarthritis outcome scale was 86.7 points, and mean range of motion was 88°. Only two patients required perioperative transfusion. Complication rate was 27.8% and included two infections, two prosthesis stiffness, and one case of recurrent hemarthrosis. Conclusion: After appropriate medical optimization and with prompt rehabilitation, TKA can be performed in hemophilic patients with good clinical results and survivor rates comparable to nonhemophilic patients.